Enantioselective syntheses of the alkaloids cis-195A (Pumiliotoxin C) and trans-195A based on multiple applications of asymmetric catalysis - Gärtner, Martin; Qu, Jianping; Helmchen, Günter (The journal of organic chemistry, 2012)
Short enantio- and diastereoselective syntheses of the decahydroquinoline alkaloids cis- (pumiliotoxin C) and trans-195A are presented. Key steps are an enantioselective iridium-catalyzed allylic amination, a Suzuki-Miyaura coupling, a catalyst-controlled copper-catalyzed 1,4-addition, and a reductive amination.